Worker’s nasal swab: a tool for occupational exposure assessment to bioburden? - Viegas, Carla (2017)
The nose cavity is the primary portal of entry for inspired air and the first region of the respiratory tract to be in contst with bioaerosols. Nasal swab allows measurement of bioburden presence in the nose cavity and the collection is easy and painless. We intended to identify scientific papers reporting this tool as a surrogate to access exposure to microbiologic agents in occupational environments. Literature research was performed using scientific and academic databases. In 5 from 11 articles studied only one parameter was analysed, being the most common Methicillin-resistant S. aureus. Sevem studies applied cutured based-methods coupled with molecular tolls essay. Findings from two studies coroborate the use of nasal swab as a tool to complement the occupational exposure assessements, since was found association between the nasal swabs results and the occupational microbiota also assessed. Nasal swabs analyses should comprehend culture based-methods and molecular tools assay.